ANALYSIS OF LAND COVER (LULC) DYNAMICS OF A SPECIFIC AREA BASED ON GIS AND REMOTE SENSING TECHNOLOGIES - Ahmadjonov Ilknur; Tobirov Odiljon (TADQIQOTLAR, 2025)
Abstract:  The  assessment  of  territorial  potential  based  on  natural  and geographical factors plays a crucial role in sustainable regional planning and resource management.  This  article  explores  methodological  approaches  for  evaluating  the spatial  characteristics  of  a  selected  region  using  Geographic  Information  Systems (GIS) and related geospatial technologies. The study integrates natural indicators such as relief, climate, land cover, hydrology, and landscape diversity to analyze their spatial distribution and functional significance. GIS-based spatial analysis, thematic mapping, and multi-criteria evaluation methods are applied to identify areas with high potential and  development  constraints.  The  results  demonstrate  that  geospatial  technologies provide an effective framework for synthesizing heterogeneous environmental data and supporting evidence-based territorial planning. The findings contribute to improving regional assessment methodologies and offer practical insights for sustainable land use planning, environmental management, and sectoral development strategies.